Java Contract In Rubber Plantation In Sintang At The End Of The 19th Century - Eka Jaya Putra Utama; Basuki Wibowo; Muhammad Syaifullah (Cita Konsultindo Research Center, 2023)
The aim of the study was to find out the Javanese Rubber Plantation Contracts in Sintang at the end of the 19th century. Analytical descriptive research with historical methods, stages of data collection through direct observation, interviews and documents. Conducting data analysis through source criticism, data interpretation, and writing in historical studies. The results showed that Sintang has a soil structure and a supportive climate for rubber trees, so it is very strategic to become a quality rubber production area. At the end of the 19th century, the Dutch government strengthened culturstelsel politics in Sintang. Rubber seeds imported from Java are ready to be planted. The workforce comes from the natives and also comes from Java. Local rulers and traders played a role in the plantation system, while the Dutch government had the right to regulate rubber prices. Workers from Java are identified by the local people as contract Javanese. Javanese life Contracts in Sintang were borne by the Dutch company and government.